2005
DOI: 10.1038/sj.onc.1209287
|View full text |Cite
|
Sign up to set email alerts
|

Full-length ADAMTS-1 and the ADAMTS-1 fragments display pro- and antimetastatic activity, respectively

Abstract: The exact role of a disintegrin and metalloproteinase with thrombospondin motifs-1 (ADAMTS-1) and the underlying mechanism of its involvement in tumor metastasis have not been established. We have now demonstrated that overexpression of ADAMTS-1 promotes pulmonary metastasis of TA3 mammary carcinoma and Lewis lung carcinoma cells and that a proteinase-dead mutant of ADAMTS-1 (ADAMTS-1E/Q) inhibits their metastasis, indicating that the prometastatic activity of ADAMTS-1 requires its metalloproteinase activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
159
2
10

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(173 citation statements)
references
References 66 publications
(87 reference statements)
2
159
2
10
Order By: Relevance
“…19 This activity was dependent on protease activity of ADAMTS1, which also mediated activation of the cell surface EGF-like ligands amphiregulin and heparin binding-EGF. A similar mechanism was demonstrated by overexpression of both MMP1 and ADAMTS1 proteases in weakly metastatic MDA-MB231 breast cancer sublines, resulting in augmented paracrine release of EGF-like ligands and enhanced bone metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 This activity was dependent on protease activity of ADAMTS1, which also mediated activation of the cell surface EGF-like ligands amphiregulin and heparin binding-EGF. A similar mechanism was demonstrated by overexpression of both MMP1 and ADAMTS1 proteases in weakly metastatic MDA-MB231 breast cancer sublines, resulting in augmented paracrine release of EGF-like ligands and enhanced bone metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…17 Overexpression of full-length ADAMTS1 in Chinese hamster ovary (CHO) cells enhanced growth of tumor xenografts in nude mice, 18 and overexpression of active ADAMTS1 promoted pulmonary metastasis of murine mammary carcinoma (TA3) and Lewis lung carcinoma cells, but catalytically inactive mutant ADAMTS1 prevented metastasis. 19 Thus, the protease action of ADAMTS1 is predicted to participate in the ECM remodeling that promotes metastasis.…”
mentioning
confidence: 99%
“…Dysregulation of ADAM and ADAMTS expression has been reported in different types of cancer by RT-PCR profiling and microarray analysis [64][65][66][67]. The picture is rendered complex by the existence of different isoforms resulting from alternative splicing described in ADAM-8, -9, -10, -11, -12, -15, -19, -22, -28, -29, -30 and -33 or ADAMTS-4 and TS-6 genes [36,50,51,[68][69][70][71][72][73][74][75][76][77] or from putative post-translational modulations [23] resulting from a processing of the molecule by the metalloproteinase domain itself [78] or by other MMPs [79].…”
Section: Implication Of Adams and Adamtss In Physiology And Pathologymentioning
confidence: 99%
“…Among those, it is worth noting that ADAMTS-1 comprises TSP-1 repeats which may contribute to the antiangiogenic activity by trapping vascular endothelial growth factor (VEGF) 165 [100,102]. Taking these data together, ADAMTS-1 C-terminal domain should be considered as an anti-tumour and anti-metastatic region [78,103]. The ADAMTS-1 story will probably mature in the next few years since some authors have also shown that overexpression of full-length ADAMTS-1 in CHO cells enhances tumour growth [103] and promotes pulmonary metastasis of TA3 mammary carcinoma or Lewis lung cells [78].…”
Section: Roles Of Adams and Adamtss In Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation